2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--29726
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Augmented Reality for the Development of Spatial Reasoning Ability

Abstract: and then his M.S. and Ph.D. in Computer Science from the University of California, Berkeley. His research considered various user interfaces for humancomputer interaction among users with a wide range of technology skills. Bell later completed a post doc at UC Berkeley focused on teaching programming to non-computer science majors, and the development of spatial reasoning abilities for engineering students. Bell has worked at Michigan State University since 1995. His work focused on the development of K-12 tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Multiple studies have highlighted the use of AR as a visualization tool to enhance the learning experience of students (Allen et al, 2011;Bell et al, 2018;Dünser et al, 2012;Schiavone, 2020). Allen et al (2011) noted that AR helped subjects visualize the intention of the design, and Dünser et al (2012) suggested that AR has the potential to assist in the learning of 3D concepts.…”
Section: Augmented Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have highlighted the use of AR as a visualization tool to enhance the learning experience of students (Allen et al, 2011;Bell et al, 2018;Dünser et al, 2012;Schiavone, 2020). Allen et al (2011) noted that AR helped subjects visualize the intention of the design, and Dünser et al (2012) suggested that AR has the potential to assist in the learning of 3D concepts.…”
Section: Augmented Realitymentioning
confidence: 99%
“…Allen et al (2011) noted that AR helped subjects visualize the intention of the design, and Dünser et al (2012) suggested that AR has the potential to assist in the learning of 3D concepts. Studies by Bell et al (2018) and Schiavone (2020) highlighted the ability of AR to enhance the spatial visualization skills and reasoning of low-performing students.…”
Section: Augmented Realitymentioning
confidence: 99%
“…have benefit for developing spatial reasoning [4], and is several times greater than what was reported for a prior study of the use of an augmented reality app [18]. To answer our first question, namely, whether extended time in a handheld augmented reality app led to greater spatial reasoning gains than taking a conventional class alone, we did a quantitative analysis of the change in test scores on the PSVT:R assessment.…”
Section: Resultsmentioning
confidence: 94%
“…See Figure 3 for examples of various games and activities that were included. Bell, et al [18] hypothesized that limited time in an augmented reality app might explain the minimal benefits of the app. Since a key question for this study was whether or not additional time in using an augmented reality app might lead to greater benefit, the app was designed to promote longer engagement.…”
Section: Figure 2: Sample Of the Digital Objects In The Augmented Reality Appmentioning
confidence: 99%
See 1 more Smart Citation